Evaluation in the Kurdish Media Institutions (A Descriptive Study Survey) - Saeed Fathu’llah, Ibraheem; Ali Ahmed, Fouad (ALBAHITH ALALAMI, 2013)
The importance of evaluation depends on many institutions, whether governmental or private, including media institutions, rely on the list to evaluate the weight of things and appreciation, as well as judging things, achievements, and everything related to the institution is concerned. Because through evaluation, institutions can recognize weaknesses and strengths. It is also an effective tool for management review, through which the institution can review everything related to planning and decision-making, leadership, incentives and other administrative matters. Therefore, this study attempts to shed light on the evaluation process, its basics and its importance in general and in the Kurdish media institutions as a model in particular. The researchers, in this research, adopted the methodological and scientific methods to highlight the evaluation in media institutions through research in both theoretical and field aspects. After discussing the results and in the light of the objectives of this research, the researchers concluded several important points as recommendations and suggestions.